2016
DOI: 10.1080/19336934.2016.1174355
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutants of theauberginegene

Abstract: Aubergine is an RNA-binding protein of the Piwi clade, functioning in germline in the piRNA pathway that silences transposons and repetitive sequences. Several mutations of this gene exist, but they mostly result in truncated proteins or correspond to mutations that also affect neighboring genes. We have generated complete aubergine knock-out mutants that do not disrupt the neighboring genes. These novel mutants are characterized by PCR and sequencing. Their nature is confirmed by female sterility and by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The majority of the crystal-Stellate modifiers has a role in the silencing of germinal and somatic transposons and participates in the primary as well as in the ping-pong pathway. Interestingly, mutants for these genes affect fertility, at various degrees, both in females and males (Pane et al., 2007; Specchia et al., 2008, 2017; Specchia and Bozzetti, 2009; Bozzetti et al., 2012; Sahin et al., 2016).…”
Section: The Role Of Dfmr1 In the Pirna Pathwaymentioning
confidence: 99%
“…The majority of the crystal-Stellate modifiers has a role in the silencing of germinal and somatic transposons and participates in the primary as well as in the ping-pong pathway. Interestingly, mutants for these genes affect fertility, at various degrees, both in females and males (Pane et al., 2007; Specchia et al., 2008, 2017; Specchia and Bozzetti, 2009; Bozzetti et al., 2012; Sahin et al., 2016).…”
Section: The Role Of Dfmr1 In the Pirna Pathwaymentioning
confidence: 99%
“…In order to better elucidate this involvement, we decided to investigate belle function in the gonads, where the role of the different components of the piRNA pathway is almost entirely known (Vagin et al, 2006; Brennecke et al, 2007; Klattenhoff and Theurkauf, 2008; Li et al, 2009; Malone et al, 2009; Khurana and Theurkauf, 2010; Senti and Brennecke, 2010; Czech et al, 2013; Handler et al, 2013; Muerdter et al, 2013; Iwasaki et al, 2015). Our group has identified some key components of the piRNA pathway, like aubergine, hsp83, dFmr1 (Specchia et al, 2008, 2010, 2017; Specchia and Bozzetti, 2009; Bozzetti et al, 2015) and demonstrated that TEs and repetitive sequences like Stellate are transcriptionally activated as a consequence of mutations in these piRNA genes (Aravin et al, 2001, 2003; Nishida et al, 2007; Specchia and Bozzetti, 2009; Bozzetti et al, 2012, 2015; Malone et al, 2015; Sahin et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…They also co-localize at the “nuage” of the germline where, Argonaute, Tudor and many other factors are also located for an efficient TE silencing (Lasko and Ashburner, 1990; Lim and Kai, 2007; Lasko, 2013; Bozzetti et al, 2015). However, in contrast to the majority of piRNA-related genes (Nishida et al, 2007; Specchia et al, 2008, 2010, 2017; Specchia and Bozzetti, 2009; Bozzetti et al, 2015; Sahin et al, 2016), belle seems not to be involved in the crystal-Stellate regulatory pathway, since mutant flies did not exhibited Stellate-made crystalline aggregates in the spermatocytes (Supplementary Information and Supplementary Figure S6). This observation well-agrees with the demonstration that belle EY 08943 mutant does not show an increase of RNA for TEs and repetitive sequences like Stellate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many proteins involved in piRNAs biogenesis and transposon silencing, such as Aubergine, Ago3, Vasa, Krimper, Tudor, Spindle-E, Tejas, and Kumo/Qin are localized in the nuage [ 51 , 61 , 83 , 84 , 85 , 86 , 87 , 88 ]. Although for some of these proteins the molecular mechanism of the piRNA pathway is not completely clarified, the complex framework of interactions and actions continues to be enriched with new discoveries.…”
Section: The Pirna Pathway In Drosophila Gonadsmentioning
confidence: 99%